Design and Realization of PC-based Control Demonstration Tool for Building Security Simulation using Embedded PC - Erwani Merry Sartika; Indra Maulidin; Tara Anggada Putra (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2018)
Demonstration mode is a method used to show a process or work of an object. Demonstration methods can be used to illustrate information to others, predict what will happen, facilitate different types of explanations, and some unfamiliar issues can be asked immediately when a process is demonstrated to be clearly answered. Companies in particular that sell electrical appliances use demo tools to explain the various control systems offered, or how to use the tools they sell. Demo tools are needed to explain the benefits of the control system and the use of the tools. Through automated gate control systems, automatic lights, and alarm functions, the simulation of building security systems becomes the case for the community. The development of industrial technology in the present can not be separated from the role of industrial automation. Industrial automation or numerical control is the use of control systems as well as computers used to control industrial machines and process controls to replace human power carriers. PC based control system is a high-ability control platform. The demonstration tool simulates a security system in the form of a digital output for LED lights whose sequence depends on the given digital input (push button and switch) and smart house applications. Analog input is also implemented, but for analog outputs the voltmeter does not generate the correct voltage value when the potentiometer value changes. This is because there is a loading on the voltmeter so that the output that appears on the voltmeter becomes much smaller than it should be.